Evaluation of an Alkaline Electrolyte System for Al-Air Battery. (23rd September 2015) - Sun, Zegao; Lu, Huimin; Hong, Qingshui; Fan, Liang; Chen, Chunbo; Leng, Jing
Abstract : The performance of Al–air batteries in 4 M NaOH containing ZnO or ZnO/cetyl trimethyl ammonium bromide (CTAB) hybrid inhibitor is studied by constant current discharge test. The characteristics of aluminum anodes after discharge are investigated by scanning electron microscopy (SEM), and energy dispersive analysis of X–ray (EDAX). The corrosion behavior of aluminum electrodes in 4 M NaOH containing ZnO or ZnO/CTAB is studied by means of hydrogen collection and potentiodynamic polarization. SEM and EDAX results indicate that CTAB can greatly improve the deposition of zinc so that a uniform and compact zinc layer covers on the aluminum surface.